The Emergence of Pragmatic Markers from Chinese Compounds in Chinese, Japanese and Korean - Higashiizumi, Yuko,; Shibasak, Reijirou, (Language and Linguistics E-Books Online, Collection 2025., 2025)
The Emergence of Pragmatic Markers from Chinese Compounds in Chinese, Japanese and Korean offers a new perspective on the evolution of pragmatic markers in language contact and grammaticalization, drawing on data-driven and diachronic studies of Chinese compounds. All the contributors to this volume address the issue of whether compounds of Chinese origin have grammaticalized into discourse markers or pragmatic markers from their earlier lexical forms, either similarly across these languages or in distinct, language-specific ways. The findings presented in this volume suggest that the written-contact-based grammaticalization in these East Asian languages is fundamentally different from the spoken-contact-based grammaticalization reported in many previous studies.